Prognostic Value of Cardiac Troponin I for In-hospital Recovery in Patients with ST-Elevation Myocardial Infarction (Journal of Rangpur Medical College, 2025)
Introduction: ST-elevation myocardial infarction (STEMI) remains a common cause of cardiovascular mortality, with accurate risk stratification for the appropriate management of the patient. Cardiac troponin I (cTnI) has been identified as a potential prognostic biomarker, as well as in its diagnostic role. Objective: This study aimed to evaluate the prognostic significance of cardiac troponin I level for in-hospital recovery and complications in patients with STEMI. Methods: A cross-sectional study was conducted on 100 STEMI patients aged 30-70 years. The patients were categorized into three groups based on serum troponin I concentration: